PENGARUH LIKUIDITAS, PROFITABILITAS, SOLVABILITAS, DAN PERTUMBUHAN PENJUALAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN TEKSTIL YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020 – 2024 - Siti Fatimah Azzahra; Siagian, Ade Onny (Jurnal Bisnis Terapan, 2025)
Indonesian textile companies face significant challenges in maintaining their financial stability, especially considering economic changes and strong competition in the market. One of the main risks is financial distress, which is a state when a company begins to experience financial pressure that can lead to bankruptcy. The purpose of this study is to determine how financial ratios such as Liquidity (Current Ratio), Profitability (Return on Asset), Solvency (Debt to Equity Ratio), and Sales Growth impact Financial Distress in textile companies listed on the Indonesia Stock Exchange from 2020 - 2024. The data used for this study came from the annual financial statements of eight sample textile companies. A quantitative approach, multiple linear regression method, was used. The results of this study indicate that the liquidity and solvency ratios have a significant effect on financial distress partially, the four factors simultaneously affect financial distress. These results can help company management make the right financial decisions to continue operating in the future.